A Reflex Protocol for Creatinine Testing Reduces Costs and Maintains Patient Safety - Lehman, Christopher M; Pearson, Lauren; Salmond, Jennifer; Raphael, Kalani; Schmidt, Robert L (Laboratory medicine, 2019)
The Jaffe and enzymatic methods are the 2 most common methods for creatinine measurement. The Jaffe method is less expensive but subject to interferences. Some laboratory scientists have called for the Jaffe method to be retired. To determine the most cost-effective and safe protocol for creatinine measurement. We performed a retrospective database review of all outpatient creatinine measurements for 1 year, testing the risk-based reflex testing protocol we had implemented for creatinine measurement. Samples were first measured using the Jaffe method and were reflexed to the enzymatic method if the estimated glomerular filtration rate (eGFR) was between 55 and 65 mL per min per 1.73 m2. There were 104,530 creatinine measurements, of which 11,420 (10.9%) were reflexed to the enzymatic method. The Jaffe method had a positive bias of 0.08 mg per dL (-6.14 mL/min/1.73 m2 eGFR). A total of 3.4% of the paired reflexed specimens were discordant. Also, 133 (1.2%) of the Jaffe results were classified as false negatives and 3411 (29.9%) were classified as false positives. None of the false-negative results and 5 of the false-positive results were considered clinically significant. Using the reflex protocol saved approximately $40,000 per year. The reflex protocol for creatinine measurement can reduce costs with acceptable risk.